PENGARUH MEDIA SOSIAL TERHADAP PELUANG USAHA WARGA RT 04 RW 08 KELURAHAN TUGU DEPOK - Dian Novita; Septian Wulandari (JABE (Journal of Applied Business and Economic), 2022)
This study aims to determine how much influence social media has on business opportunities in RT 04 RW 08 Tugu Depok. The research method is descriptive statistics with the sample in the study being residents of RT 04 RW 08 Tugu Depok. The number of samples as many as 52 samples with a sampling technique that is random sampling. The data collection technique is distributing questionnaires to residents containing questions that include indicators from Social Media including Context (), Communication (), Collaboration (),), and Connections (). Testing the validity of an instrument can be seen from the value of the loading factor with a value of more than 0.50 meaning 15 questionnaires are declared valid for the research instrument. The results of the reliability test were carried out using the conbarch's alpha value and the results were 0.913. The conclusion obtained is that there is a significant effect on social media with indicators of context, communication, collaboration, and connection on business opportunities in RT 04 RW 08 Tugu Depok, there is no significant effect on indicators of communication and connection to business opportunities in RT 04 RW 08 Tugu Depok, there is a significant influence on context indicators and collaboration on business opportunities in RT 04 RW 08 Tugu Depok, the indicator that has the most influence on business opportunities is collaboration with a t-count value of 5.943.